An Analysis on The Use of Lexical Cohesion in Studentsâ Writing - Zulianti, Hajjah (Lentera: Jurnal Ilmiah Kependidikan, 2018)
This research aims to describe the lexical cohesion used in studentsâ writing, and to find out the highest frequency of lexical ties in studentsâ writing. In conducting the research, the researcher uses descriptive qualitative method. The researcher uses a documentation to collect the data. The data are the studentsâ scientific writing tasks on fifth semester at STKIP PGRI Bandar Lampung. In analyzing the data, the researcher uses the procedure such as recording the data in the data card, categorizing the data based on the types of lexical cohesion, summing up the total number of lexical cohesion  frequencies, describing the data  and drawing conclusion. The result shows that the types of lexical cohesion in studentsâ writing are repetition, synonymy, antonymy, and meronymy. Repetiton becomes the prominent types of lexical cohesion used in studentsâ writing. Meanwhile the hyponymy is the lowest frequency of occurrence in their writings.